BOT–ENGINEER: A system to Create Chatbots - Souza, Ravino D; DaCosta, Kai; Cardozo, Deston; Barretto, Maria Christina (International Journal of Computer Sciences and Engineering, 2025)
Digital Assistants driven by Artificial Intelligence (A.I.) are becoming increasingly popular .These assistants can send users updates on live data, help them know about the traffic situation on the way to work or home. All that the user has to do is ask. Due to increasing technologies, large amount of data gets generated. Digital assistants are changing the way people search for information, making it part of regular conversation. In this paper, we present a BOT-ENGINEER, a system that is designed to create chatbots. It uses intent classification and entity extraction to find what the user has said and meaningful keywords that represent actual data respectively